TÉCNICA DE SLING: AVALIAÇÃO DOS RESULTADOS COMPARANDO FAIXA DE POLIPROPILENO INDUSTRIALIZADA E ARTESANAL - Sousa, Antonio de Pádua Silva (2008)
This study proposes to evaluate the results post stress urinary incontinence surgery (SUI) using the Sling technique and utilizing a range of polypropylene sub urethral manually manufactured (Marlex®), and laboratory made (Advantage®), comparing the results in both groups and prostheses costs. The sample used was of 39 women carriers of SUI resulting from hyper mobility of the bladder neck and/or sphincteric incompetence determined by clinical evaluation and urodynamic studies. The criterion considered was the exclusion of diabetes mellitus, previous extended pelvic surgeries and previous radiotherapy. The patients were split in 2 groups. Group 1 Patients from the department of Urology at the University Hospital of the Federal University of Maranhao (19 patients) and Group 2 Patients from private clinics (20 patients). Group 1 used the manually manufactured polypropylene sub urethral while group 2 used the laboratory made. Patients were evaluated in between thirty, sixty and ninety days post surgery comparing the following variables: Average surgery time, hospitalization time, difficulty to urinate, length of time using the post surgery probe, normalization of urinary jet, involuntary urine loss, level of satisfaction regarding the surgery, urodynamic alterations and probe costs. The average surgery time was of 43 25 in Group 1 and 51 42 Group 2. As to difficulty to urinate post surgery, in Group I, one hundred percent (100%) of the patients presented no difficulties while in Group 2; ninety four point seven percent (94.7%) were able to urinate properly. Regarding the probe use one hundred percent (100%) of the patients from both groups were free from it by the end of this study. All patients from both groups presented normal urinary jet during the last evaluation. In Group 1 one hundred percent (100%) of the patients did not accuse urine loss, while in Group 2 it was ninety four point seven percent (94.7%) at the ninetieth day. The level of satisfaction was of one hundred percent (100%) of the patients from Group 1 while one patient in Group 2 considered the surgery unsuccessful. The evaluation urodynamic presented non inhibit contraction of low vesical pressure in eleven point one percent (11.1%) in Group 1 and ten point five percent (10.5%) in Group 2. There were no complications in both groups. Occurrences observed: burning micturition and urinary urgency spontaneously disappeared by the end of this study and did not have any relations with sub urethral meshes. We can conclude the use of polypropylene mesh (Marlex ®) manually manufactured can also be used in Sling surgeries, saving on resources and having similar results to the use of the laboratory made version.